2011
DOI: 10.1074/mcp.m110.004804
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Regulated Secretome Components During Skeletal Myogenesis

Abstract: Myogenesis is a well-characterized program of cellular differentiation that is exquisitely sensitive to the extracellular milieu. Systematic characterization of the myogenic secretome (i.e. the ensemble of secreted proteins) is, therefore, warranted for the identification of novel secretome components that regulate both the pluripotency of these progenitor mesenchymal cells, and also their commitment and passage through the differentiation program. Previously, we have successfully identified 26 secreted protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 167 publications
(83 reference statements)
2
67
0
1
Order By: Relevance
“…High expression of OGN inhibits metastatic behavior and decreases gelatinase activity of murine hepatocarcinoma Hca-F cells (23,24). In this study the levels of OGN were elevated during osteoblast differentiation, which was consistent with a previous study (25). Moreover, some comparative microarray studies revealed that OGN is one of the mechanosensitive genes that mediates an anabolic response of mechanical loading in mice and in osteoblasts using a rotating wall vessel and a random positioning machine (26,27).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…High expression of OGN inhibits metastatic behavior and decreases gelatinase activity of murine hepatocarcinoma Hca-F cells (23,24). In this study the levels of OGN were elevated during osteoblast differentiation, which was consistent with a previous study (25). Moreover, some comparative microarray studies revealed that OGN is one of the mechanosensitive genes that mediates an anabolic response of mechanical loading in mice and in osteoblasts using a rotating wall vessel and a random positioning machine (26,27).…”
Section: Discussionsupporting
confidence: 77%
“…In our data the levels of OGN were decreased by activation of ALK2 signaling, which pathologically converts muscle tissues to bone in fibrodysplasia ossificans progressiva, and the levels of OGN increased when myoblastic cells differentiated into myotubes upon horse serum treatment. Moreover, Chan et al (25) recently reported that OGN was included in differentially up-regulated secretome components during skeletal myogenesis in C2C12 cells in a recent study. These findings suggest that OGN might play some important role in muscle.…”
Section: Discussionmentioning
confidence: 99%
“…At present, different proteomic techniques allow for in-depth analysis of the secretome, the global pattern of secreted proteins. Secretome analysis is important in revealing complex cellular processes that require communication and signaling between the cells, and it has recently been applied to analyze the signaling pathways related to cell differentiation (19,20), cancer (21,22), and immune responses (23)(24)(25). In the present work we have characterized the secretome of human primary macrophages that have been activated simultaneously by microbial signal lipopolysaccharide (LPS) and endogenous danger signal MSU to get a global view of macrophage response to combined PAMP and DAMP stimulation.…”
Section: Monosodium Urate (Msu) Is An Endogenous Danger Signal That Imentioning
confidence: 99%
“…As part of its extracellular signaling pathway, skeletal muscle secretes myokines that participate in myogenesis, angiogenesis, and nutrient generation in response to factors such as metabolic disorders, including insulin resistance, and exercise (11)(12)(13). Some myokines, including IL-6, IL-8, IL-15, and fibroblast growth factor 21, and brain-derived neurotrophic factor (14), are induced by exercise.…”
mentioning
confidence: 99%